2002
DOI: 10.1177/152692480201200408
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Potential Candidates for Heart and Heart-Lung Transplantation to Xenotransplantation

Abstract: Potential heart and heart-lung recipients and their caregivers have limited information about xenotransplantation and are currently unsure about the acceptability of this procedure. Although this uncertainty may be due to their lack of information about this intervention, it may also reflect concerns about the morality of breeding animals solely to provide organs for transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Ethical concerns were not as important as seen in other studies and concerns about animal rights have not been mentioned at all by our patients. It seems that patients who, because of their diseases, already spent time thinking about transplantation in general are more concerned abut medical issues (8,9), whereas the general public has more concerns about ethical issues (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ethical concerns were not as important as seen in other studies and concerns about animal rights have not been mentioned at all by our patients. It seems that patients who, because of their diseases, already spent time thinking about transplantation in general are more concerned abut medical issues (8,9), whereas the general public has more concerns about ethical issues (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…However, in 1999, a large German study showed that transplant recipients had a more positive attitude toward xenotransplantation than patients on the waiting list for an organ (7). Candidates for organ transplantation generally state that they have only limited knowledge about xenotransplantation, making decisions complicated (8). The importance of appropriate information was shown in a study of patients with type 1 diabetes asked for their opinion on pig pancreatic islet cell transplantation.…”
Section: Acceptance Rates Of Xenotransplantation In Different Cohortsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tables 1 and 2 present data from surveys conducted with people who have received or are waiting an allotransplant, as well as potential allotransplant recipients. While acceptance of XTP varies greatly amongst these populations, ranging from 100 percent (Frati et al 2001) to 14 percent (Long et al 2002), the acceptance rates generally range from 60 to 83 percent (as seen in Martínez‐Alarcón et al 2005). Some of this research seems to indicate that the severity of an individual’s health status impacts on acceptance of XTP.…”
Section: Public Perceptions and Survey Researchmentioning
confidence: 99%
“…However other factors, such as what type of information is supplied and how it is presented and personal characteristics, can influence an individual's decision-making. For example, Arundell et al (1994), Arundell and McKenzie (1997), Mohacsi et al (1997), and Long et al (2002), did not receive an overwhelming acceptance of XTP from people who were waiting for or had received an allotransplant (see Table 1). Thus, it cannot be presumed that compromised health and a desire to survive translates into XTP acceptance.…”
Section: Public Perceptions and Survey Researchmentioning
confidence: 99%